Biomarkers in aortic dissection, including specific causes of troponin elevation - Koraćević Goran; Antonijević Nebojša; Ćosić Vladan; Pavlović Milan; Kostić Tomislav; Zdravković Marija; Cvetković Tatjana; Tomašević Miloje; Ćirić-Zdravković Snežana; Krstić Nebojša; Damjanović Miodrag (Vojnosanitetski Pregled, 2016)
nema